Compact Dual Port UWB MIMO Antenna with WLAN Band Rejection - Firdaus Firdaus; Intan Aprillia Ikhsan; Rahmadi Kurnia; Ikhwana Elfitri (Jurnal Elektronika dan Telekomunikasi, 2024)
This research presents the design of a compact dual-port UWB MIMO antenna. The primary challenge in designing UWB MIMO antennas lies in achieving a low-frequency band of 3.1 GHz while maintaining a small size. By modifying the patch shape to a tapered configuration and incorporating an inset feed and a slit for WLAN notch band, a rectangular monopole patch antenna successfully overcomes these limitations. The MIMO configuration of this antenna achieves a wide UWB bandwidth of 3.1-12 GHz with a compact dimension of 20×28.5×1.6 mm. The antenna exhibits excellent characteristics, including low mutual coupling (-15 dB), maximum gain of 3 dBi, low ECC (<0.01), high diversity gain (<9.95), low TARC (< -20 dB), and nearly omnidirectional radiation pattern. These results demonstrate the suitability of the proposed antenna design for UWB applications.